FUNGSI PEJABAT PENGELOLA INFORMASI DAN DOKUMENTASI DALAM MEMBERIKAN PELAYANAN INFORMASI PUBLIK DI DAERAH ISTIMEWA YOGYAKARTA - Winarni Winarni; Fransisca Romana Harjiyatni; Takariadinda Diana Ethika (Universitas Janabadra, 2022)
Abstract In this thesis the author takes the title Function of Information Management and Documentation Officials (PPID) in providing Public Information Services in the Special Region of Yogyakarta. This study discusses how the main PPID is in providing information services in the Special Region of Yogyakarta based on the provisions of the applicable legislation. By using normative research methods and approaches to legislation and conceptual and qualitative data processing, it is concluded that the main PPID in the Department of Communications and Information Technology DIY has implemented Law Number 14 of 2008 concerning Public Information Disclosure. However, there are several factors that influence PPID in carrying out its function in realizing public information services in DIY including Juridical factors, Structural factors, Apparatus factors / Service Officers. Some of these factors are also obstacles faced by PPID in implementing Law No. 14 of 2008 concerning Openness of Public Information, namely, the low commitment of the leadership of public agencies, limited Personnel / Human Resources (HR) who specifically handle the provision and management of public information. information services in several OPDs within the DIY Regional Government, including an understanding of the duties and functions of some OPDs regarding the provision of a Public Information List and a list of excluded information and related to inadequate budgets